Matching Fabric Based on Wavelet Kernel Signature (WKS) and Drape Indicators (Journal of Fiber Bioengineering and Informatics, 2019)
The drape performance of the fabric is an important part of the fabric style, as well as a special expressionof the structural parameters and mechanical properties. The comprehensive drape performance of fabriccan support fabric matching. This study was conducted to match fabric based on 3D triangular meshesof draped fabrics. Firstly, the three-dimensional (3D) point cloud of draped fabric was scanned with aself-built 3D scanning device followed with triangulation. Secondly, three drape indicators, i.e., drapecoefficient, the number of fabric drape nodes, and the solid rate of a draped fabric was extracted, aswell as the wavelet kernel signatures (WKS) of triangular meshes. The WKS of vertices on the 3Dboundary was selected and clustered into different classes with K-Means. With the cluster centers, theWKS of vertices on the boundary was encoded into a vector with a fixed length. Finally, two methodsfor matching fabrics were proposed based on WKS+DR and a vector consisting of three drape indicatorsseparately. The results show that WKS+DR outperforms the vector consisting of drape indicators incharacterizing the drape configuration details of a draped fabric. The accuracy of the method based onWKS+DR could reach 89.6%. The fabrics obtained with this method are close to the matching fabricsin both drape-ability and details of a triangle surface.
Keywords: Fabric Matching; Draped Fabric; Triangular Mesh; Wavelet Kernel Signature (WKS)